Flexible bronchoscopy in pediatric intensive care unit - Krishan Chugh; Neetu Talwar; Manish Kori; Kaustubh Mohite; Mahesh Mohite (Wolters Kluwer Medknow Publications, 2023)
Flexible bronchoscopy (FB) is a very rewarding procedure in the evaluation and management of appropriately selected children with respiratory issues in pediatric intensive care unit (PICU). An understanding of the alterations in respiratory physiology (airway resistance, compliance, and air exchange) during FB is absolutely essential for the safety of the child. To reduce discomfort and other side effects of FB it is necessary to optimize the condition of the child including sedation, analgesia, paralysis, ventilator settings, and cardiovascular status. With advancements in technology and instrumentation many interventional procedures can be performed safely and effectively using access to the airway through the endotracheal tube, tracheostomy tube, or Laryngeal Mask Airway (LMA). Close monitoring during and after FB minimizes complications.